2014
DOI: 10.1007/978-3-319-13770-4_3
|View full text |Cite
|
Sign up to set email alerts
|

Models for Logics and Conditional Constraints in Automated Proofs of Termination

Abstract: Abstract. Reasoning about termination of declarative programs, which are described by means of a computational logic, requires the definition of appropriate abstractions as semantic models of the logic, and also handling the conditional constraints which are often obtained. The formal treatment of such constraints in automated proofs, often using numeric interpretations and (arithmetic) constraint solving, can greatly benefit from appropriate techniques to deal with the conditional (in)equations at stake. Exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 17 publications
(29 reference statements)
0
18
0
Order By: Relevance
“…This observation was a main motivation to develop the idea of convex polytopic domain [12] as a sufficiently simple but flexible approach to obtain a variety of domains that can be used in proofs of termination and which are amenable for automation [10]. The research in this paper closes some gaps left during these developments and provides a basis for the implementation of P RP in the OT Framework by means of the automatic generation of logical models for order-sorted first-order theories.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This observation was a main motivation to develop the idea of convex polytopic domain [12] as a sufficiently simple but flexible approach to obtain a variety of domains that can be used in proofs of termination and which are amenable for automation [10]. The research in this paper closes some gaps left during these developments and provides a basis for the implementation of P RP in the OT Framework by means of the automatic generation of logical models for order-sorted first-order theories.…”
Section: Discussionmentioning
confidence: 97%
“…In [10] we have shown that convex domains [12] provide an appropriate basis to the automatic definition of algebras and structures that can be used in program analysis with order-sorted first-order specifications. In the following definition, vectors x, y ∈ R n are compared using the coordinate-wise extension of the ordering ≥ among numbers which, by abuse, we denote using ≥ as well:…”
Section: Interpreting Predicates Using Convex Domainsmentioning
confidence: 99%
See 1 more Smart Citation
“…The resolution of our running example (Example 6) shows that flexibility in the definition of domains A s for sorts s ∈ S is an asset: we have simultaneously used (due to the presence of sorts) an infinite domain like N (which is typical in termination proofs) and the finite domain {0}. In order to provide an appropriate computational basis to the automatic definition of algebras and structures that can be used in program analysis with order-sorted first-order specifications, we follow [11] and focus on domains that are obtained as the solution of polynomial and specially linear constraints. In Definition 3, vectors x, y ∈ R n are compared using the coordinate-wise extension of the ordering ≥ among numbers (by abuse, we use the same symbol): x = (x 1 , .…”
Section: Order-sorted Structures With Convex Domainsmentioning
confidence: 99%
“…We also show how to transform an OS-FOL theory S into a derived parametric theory S ♯ of linear arithmetic where appropriate algorithms and constraint solving techniques can be used to give value to the parameters thus synthesizing a model of S . The convex domains introduced in [11] provide appropriate means for this. They can be used to define bounded and unbounded domains for the sorts in the OS signature.…”
Section: Introductionmentioning
confidence: 99%